MASH - Altman, Robert, 1925-2006.; Sutherland, Donald, 1935-; Gould, Elliott; Skerritt, Tom.; Kellerman, Sally; Hooker, Richard; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 1997)
Classic American war comedy focusing on the antics of three army surgeons in Korea, who develop a lunatic lifestyle to help them handle the horrors encountered everyday in their Mobile Army Surgical Hospital.
Based on the novel by Richard Hooker.
Originally released as a motion picture in 1970.
For specific added features see container or interactive features menu while viewing disc.
Music, Johnny Mandel.
Donald Sutherland, Elliott Gould, Tom Skerritt, Sally Kellerman, Robert Duvall, Jo Ann Pflug, Rene Auberjonois.
Canadian Home Video Rating: 14A.
Keywords: Hooker, Richard. -- Film adaptations; 1950-1953; Mobile hospitals -- Korea -- Fiction; Korean War, 1950-1953 -- Fiction; War films; Comedy films; Feature films; Film adaptations